2016
DOI: 10.1016/j.bjan.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurano fornece neuroproteção em lesão cerebral hipóxico‐isquêmica neonatal por inibição da apoptose

Abstract: Isoflurane showed a neuro-protective effect on hippocampal neuron injury induced by hypoxia through suppression of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…8 At present, mild hypothermia therapy is commonly used to treat HIE in clinical practice, but 40%-50% of children with severe HIE still develop serious sequelae after treatment. 9 Isoflurane (ISO) is an inhalation anesthetic that inhibits inflammation, prevents oxidative stress, and has some neuroprotective effects. 10 After many years of clinical application, it has been found that it has the characteristics of reducing intracranial pressure, reducing cerebral oxygen consumption, inducing and maintaining balance, promoting rapid recovery, and inducing few side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 At present, mild hypothermia therapy is commonly used to treat HIE in clinical practice, but 40%-50% of children with severe HIE still develop serious sequelae after treatment. 9 Isoflurane (ISO) is an inhalation anesthetic that inhibits inflammation, prevents oxidative stress, and has some neuroprotective effects. 10 After many years of clinical application, it has been found that it has the characteristics of reducing intracranial pressure, reducing cerebral oxygen consumption, inducing and maintaining balance, promoting rapid recovery, and inducing few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, an unsolved medical problem needs to be studied to elucidate the mechanism and find effective neurotherapeutic goals 8 . At present, mild hypothermia therapy is commonly used to treat HIE in clinical practice, but 40%–50% of children with severe HIE still develop serious sequelae after treatment 9 …”
Section: Introductionmentioning
confidence: 99%
“…Isoflurane is a common volatile anesthetic in the clinic and protects against ischemic brain injury [129] by suppressing apoptosis [130]. Preconditioning using a clinically relevant concentration of isoflurane can attenuate renal IRI.…”
Section: Other Anesthetics In Irimentioning
confidence: 99%
“…Isoflurane (ISO) is a common volatile anesthetic in the clinic and protects against ischemic brain injury (Cheon et al, 2017). For example, isoflurane provides neuroprotection in ischemic brain injury by suppressing apoptosis (Zhao et al, 2016). ISO post-conditioning can ameliorate intracranial hemorrhage and infarction volume in tPA-exaggerated brain injury (Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%